2016
DOI: 10.1002/cam4.679
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of monoclonal immunoglobulin gene rearrangement in conjunction with histologic B‐cell aggregates in the bone marrow of patients with diffuse large B‐cell lymphoma

Abstract: Bone marrow involvement (BMI) is a well‐known poor prognostic factor in patients with diffuse large B‐cell lymphoma (DLBCL). This study robustly investigated the significance of monoclonal immunoglobulin gene rearrangement combined with histologic B‐cell aggregates in bone marrow (BM) in the detection of a poor prognostic group. Pretreatment BM samples of 394 DLBCL patients were analyzed via the immunoglobulin gene rearrangement study and the microscopic examination. Monoclonal immunoglobulin gene rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several studies have also noted the selection pressure between remission and relapse, such as that resulting from treatments and antigens [68,[71][72][73]. Other IG repertoire-associated factors influencing the prognosis included monoclonality, the length of the HCDR3, and the abnormal ratio of functional IGK/IGL rearrangements [56,69,74,75].…”
Section: Ig Gene Rearrangement Pattern In Dlbclmentioning
confidence: 99%
“…Several studies have also noted the selection pressure between remission and relapse, such as that resulting from treatments and antigens [68,[71][72][73]. Other IG repertoire-associated factors influencing the prognosis included monoclonality, the length of the HCDR3, and the abnormal ratio of functional IGK/IGL rearrangements [56,69,74,75].…”
Section: Ig Gene Rearrangement Pattern In Dlbclmentioning
confidence: 99%
“…Cox et al [ 12 ] analyzed 151 patients with DLBCL and found that 17 cases (11.2%) had a serum monoclonal IgM component, although none were associated with MYD88L265P mutations, which indicates there is no necessary connection between monoclonal IgM and MYD88L265P. Cho et al [ 13 ] studied the relationship between the clonal status of monoclonal immunoglobulin gene rearrangement and histological B cell aggregation in the BM. The results showed that of the 394 patients with DLBCL, 32 patients had BM invasion, and only two patients with large B-cell lymphoma had no gene rearrangement detected[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al [ 13 ] studied the relationship between the clonal status of monoclonal immunoglobulin gene rearrangement and histological B cell aggregation in the BM. The results showed that of the 394 patients with DLBCL, 32 patients had BM invasion, and only two patients with large B-cell lymphoma had no gene rearrangement detected[ 13 ]. This suggests that patients with BM invasion were more likely to have monoclonal immunoglobulin gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow biopsies are slowly being replaced by other methods for staging. Cho et al [ 41 ] investigated pretreatment BM samples of 394 DLBCL patients with clonality testing in addition to microscopic examination. Monoclonal immunoglobulin gene rearrangement was detected in 25 % of cases.…”
Section: Stagingmentioning
confidence: 99%